Association of Pre-existing Hypertension to The Development of Superimposed Preeclamsia - Andi Muh. Ariansyah Nazaruddin; Yusran Antonius (The Indonesian Journal of General Medicine, 2026)
Introduction: Superimposed preeclampsia (SPE), the development of preeclampsia in women with pre-existing chronic hypertension (CH), represents a high-risk obstetric condition associated with significant maternal and perinatal morbidity and mortality. Understanding the magnitude of this risk and the effectiveness of preventive interventions is critical for improving outcomes in this vulnerable population. Methods: This systematic review synthesized evidence from 40 studies, published between 2005 and 2025. Studies were screened and included if they examined pregnant women with CH, reported on SPE as an outcome, provided quantitative data on the association, and had appropriate study designs. Data were extracted on study characteristics, population demographics, definitions of CH and SPE, incidence rates, risk factors, effectiveness of preventive interventions (e.g., low-dose aspirin, antihypertensives, metformin), predictive markers, and secondary maternal/perinatal outcomes. Results: The pooled incidence of SPE among women with CH was 25.9% (95% CI: 21.0-31.5%), representing a 5- to 8-fold increased risk compared to normotensive women (Bramham et al., 2014; Al Khalaf et al., 2019). Risk was significantly modified by renal dysfunction (even mild elevations in serum creatinine or proteinuria), uncontrolled blood pressure, and newly diagnosed CH during pregnancy (Kawakita et al., 2022; Heimberger et al., 2020; Nie et al., 2024). Meta-analyses of RCTs found low-dose aspirin (typically 60-150 mg) did not significantly reduce the risk of SPE (OR 0.83, 95% CI: 0.55-1.25), with subgroup analysis from the ASPRE trial showing a significant interaction suggesting no benefit in women with CH (Poon et al., 2017; Richards et al., 2023). However, aspirin reduced preterm birth and composite adverse neonatal outcomes. Antihypertensive treatment effectively reduced severe hypertension (RR 0.33) but had no significant impact on SPE incidence (RR 0.74, 95% CI: 0.49-1.11) (Webster et al., 2017). Promising predictive markers included the sFlt-1/PlGF ratio (particularly after 27 weeks) and second-trimester cerebrovascular hemodynamics (Scalia et al., 2024; Riskin-Mashiah & Belfort, 2005). Women with SPE had worse maternal and neonatal outcomes compared to those with preeclampsia alone. Discussion: The strong association between CH and SPE is well-established, but significant heterogeneity in incidence stems from variations in population risk profiles, diagnostic criteria, and blood pressure control. The apparent "aspirin paradox"—where aspirin is highly effective in preventing preeclampsia in other high-risk groups but not in women with CH—may indicate a distinct pathophysiology in this group, involving pre-existing endothelial and vascular damage less responsive to antiplatelet therapy. The primary benefit of antihypertensive therapy is in preventing severe maternal hypertension, not SPE. Accurate risk stratification using renal markers and achieving tight BP control are crucial management pillars. Conclusion: Chronic hypertension confers a substantially elevated risk for superimposed preeclampsia, with incidence influenced by renal function and BP control. Current evidence does not support low-dose aspirin for primary prevention of SPE in this population, though it retains benefit for reducing preterm birth. Management should focus on stringent blood pressure control, early risk stratification using renal parameters, and vigilant monitoring for predictive biomarkers. Future research should prioritize large RCTs targeting women with CH, exploring alternative preventive agents like metformin, and refining predictive models.